In situ calcite U–Pb geochronology of carbonate and clastic sedimentary rocks from the Canning Basin, Western Australia - Li, Zhen; Rankenburg, Kai; Normore, L.S.; Evans, Noreen; McInnes, Brent; Dent, L.M.; Fielding, I.O.H. (TAYLOR & FRANCIS LTD, 2023)
In sedimentary basins, the determination of the absolute timing of deposition and diagenetic events is a challenging yet critical parameter necessary in the reconstruction of paleo-fluid evolution and burial histories. Here we demonstrate the practical application of in situ calcite U–Pb geochronology on core samples from the Olympic 1 well in the Canning Basin of Western Australia. Using quantitative mineralogy and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) analytical techniques, we obtained an authigenic calcite U–Pb age of 469.7 ± 4.3 Ma for limestone in the Samphire Marsh Member of the Lower Ordovician Nambeet Formation. This precise depositional age can be independently verified using zircon thermal ionisation mass spectrometry U–Pb ages of 479.4 to 470.2 Ma determined on adjacent volcanic ash beds. Further geochronology studies on calcite cements from the Lower Ordovician Fly Flat Member sandstone from the Nambeet Formation returned a U–Pb age of 365.3 ± 5.8 Ma. This is the first study to place absolute age constraints on the diagenetic event that occluded the intergranular space in a sandstone reservoir. The calcite cementation age suggests that impairment of reservoir quality in the Fly Flat Member sandstone occurred in the Late Devonian, much earlier than major petroleum charge events in the Canning Basin. The calcite U–Pb geochronometer, when combined with complementary quantitative mineralogical analysis, can build direct temporal constraints on the depositional and diagenetic processes in both carbonate and clastic sedimentary rocks in basins worldwide.